(NgIDROLOGIQ MALYH REK (B:s [(NsBORNIK STATEJ(B] /s - (NnIKORA(B, (NwLADIMIR iWANOWI^s; (NiNSTITUT GEOFIZIKI I GEOLOGII an mOLDAWSKOJ ssrs ((NkI[INEW (B:s (N{TIINCA(B,s, 1991)
(NbIBLIOGR(B. (NW KONCE ST(B.s
Keywords: (NgIDROLOGIQs; (NrEKI MALYEs